2022
DOI: 10.1038/s41598-022-25722-0
|View full text |Cite
|
Sign up to set email alerts
|

Ocular surface microbiome in diabetes mellitus

Abstract: This cross-sectional, age- and gender-matched study included 20 eyes of non-diabetic subjects (non-DM group) and 60 eyes of type 2 diabetes mellitus (DM group). Subgroups of DM were classified by diabetic retinopathy (DR) staging into no DR (DM-no DR), non-proliferative DR (DM-NPDR), proliferative DR (DM-PDR), and by glycemic control (well-controlled DM; HbA1c < 7%, poorly controlled DM; HbA1c ≥ 7%). Conjunctival swabs were performed for ocular surface microbiome analysis using conventional culture and next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…It was postulated that vitamin D deficiency could promote ADDE instead of evaporative dry eye, as Schirmer's test between the groups was significantly different whilst the TBUT scores were comparable. Further, patients with dry eye syndrome refractive to standard administered high doses of intramuscular cholecalciferol had improvements in all outcome measures, albeit only short-term [146].…”
Section: Vitamin Dmentioning
confidence: 95%
“…It was postulated that vitamin D deficiency could promote ADDE instead of evaporative dry eye, as Schirmer's test between the groups was significantly different whilst the TBUT scores were comparable. Further, patients with dry eye syndrome refractive to standard administered high doses of intramuscular cholecalciferol had improvements in all outcome measures, albeit only short-term [146].…”
Section: Vitamin Dmentioning
confidence: 95%
“…A recent study of conjunctival swabs using conventional culture and next-generation sequencing (NGS) analysis has reported that potentially pathogenic bacteria such as Enterobacteriaceae, Neisseriaceae, Escherichia – Shigella , and Pseudomonas were more prevalent in diabetes, particularly in DR. Dissimilarities in the ocular surface microbiome were also observed between diabetic and non-diabetic groups. Interestingly, the ocular surface microbiome in poorly controlled diabetic patients differs significantly from well-controlled diabetic and non-diabetic groups [ 3 ]. In poorly controlled diabetic patients, an inappropriate immune response can cause ocular surface microbiome dysbiosis and increase the abundance of potentially harmful bacteria, especially in DR [ 123 , 124 , 125 , 126 ].…”
Section: The Impact Of Diabetes and Dr On Ocular Surface And Tear Pro...mentioning
confidence: 99%
“…With a thorough knowledge of diabetes, it is believed that oxidative stress, autoimmunity, genetics, and epigenetics play major roles in the onset of diabetes and its complications [ 2 ]. Although the most frequent and well-known ocular complication of diabetes is diabetic retinopathy (DR), with approximately one-third of all people with diabetes experiencing related vision complications, recent reports have focused on how diabetes affects the ocular surface [ 3 , 4 ], a structure similarly impacted by diabetes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, Suwajanakorn et al. ( 68 ) used next-generation sequencing analysis to demonstrate the importance of DR and glycemic control status in influencing changes in the ocular surface microbiome. Subsequent studies identified that microbes could be transferred to the retina of type 1 diabetic mice with retinopathy through gut and plasma microbiota ( 69 ).…”
Section: Microbiota and Ocular Diseasesmentioning
confidence: 99%